Retificação cilíndrica do aço VP50 utilizando o rebolo de carbeto de silício verde com a técnica de MQL - Fragoso, Kamira Miksza [UNESP]; Umberto, Derik Rios [UNESP]; Barili, Ighor Costa [UNESP]; Bianchi, Eduardo Carlos [UNESP]; da Silva, Rosemar Batista; Aguiar, Paulo Roberto [UNESP]; de Mello, Hamilton Jose [UNESP] (FapUNIFESP (SciELO), 2016)
Grinding is a high heat generation process that requires large amount of coolant, therefore, its use in large-scale lead to research and development of new lubri-cooling techniques to attend technical requirements, environmental laws, to preserve the health of operator and, whenever possible, to reduce production costs. Into this context, it is important to find solutions that maintain the same quality standards, finishing and the same technological effects. An alternative that has been used since the end of 20th. century is the MQL (minimum quantity lubrication) technique, which uses a mixture of air with low oil flow with medium pressure. The steel to be used as a specimen was VP50, widely used in industry for injection mold of thermoplastic. The grinding wheel used was green silicon carbide with vitrified binder that possess good thermal properties, high chemical stability and is recommended for grinding of ferrous and nonferrous materials. The output variables employed in this work were the surface roughness, roundness errors and microhardness. The acoustic emission signal and diametrical wear were also monitored. Analyses of the machined surfaces to evaluate the occurrence of thermal damages were also carried out via optical microscope. Results show that machining with the MQL technique outperformed the traditional coolant delivery method in terms of roundness and diametrical wear. No evidence of microstructural changes in the machined surfaces was observed after grinding with both lubri-coolant techniques.
Cylindrical grinding of VP50 steel using green silicon carbide grinding wheel with MQL technique
Keywords: Conventional lubrication; Cylindrical grinding; Grinding wheel green silicon carbide; MQL